In situ study on atomic mechanism of melting and freezing of single bismuth nanoparticles - Yingxuan Li (Nature Portfolio, 2017)
The atomic mechanisms of reversible phase transitions are challenging to probe experimentally. Here, the authors induce melting and freezing processes in bismuth nanoparticles inside a high-resolution electron microscope, observing the atom-level stages of this phase transition pathway in real time.